Pengaruh Total Quality Management dan Knowledge Sharing terhadap Kinerja Pegawai Sekretariat DPRD Kota Makassar - Hannani, Alaiyya; Rusnawati, Rusnawati (Study of Scientific and Behavioral Management, 2024)
This research aims to determine the effect of Total Quality Management and Knowledge Sharing on the performance of Makassar City DPRD secretariat employees, to determine the effect of Total Quality Management on the performance of Makassar City DPRD secretariat employees, and to determine the effect of Knowledge Sharing on the performance of Makassar City DPRD secretariat employees. This research uses quantitative research methods. This research uses primary data which directly provides data for data collection. Based on statistical research results, it can be seen simultaneously that all independent variables, namely Total Quality Management and Knowledge Sharing, have a significant effect on employee performance. The results of data analysis show that Total Quality Management and Knowledge Sharing have a positive and significant influence on the performance of Makassar City DPRD secretariat employees, the results of data analysis in the second hypothesis show that Total Quality Management has a positive and significant influence on the performance of Makassar City DPRD secretariat employees and based on the results of data analysis, In hypothesis three, Knowledge Sharing has a positive and significant effect on the performance of Makassar City DPRD secretariat employees.